2011
DOI: 10.4236/ape.2011.12003
|View full text |Cite
|
Sign up to set email alerts
|

Is There A Relationship Between the Functional Reach Test and Flexibility?

Abstract: This study examined the influence of short-term stretching and improved flexibility on functional reach (FR) performances (reach distance and rotation angle of various joints during reaching). 17 healthy male university students were assigned to either experimental and control groups based on the random assignment. A pre-test/Post-test design was used in this study. The variable factor for the experimental group was stretching (jogging for warming up and stretching). Main outcome measures were flexibility (sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…It was proven that FRT was not an appropriate indicator to differentiate between individuals with and without the risk of falling. 21 While FRT has been reported to be commonly used as a clinical test measuring the LoS, 22 fundamental differences are present between FRT and LoS. Unlike LoS, FRT measures trunk flexibility as well as LoS.…”
Section: Discussionmentioning
confidence: 99%
“…It was proven that FRT was not an appropriate indicator to differentiate between individuals with and without the risk of falling. 21 While FRT has been reported to be commonly used as a clinical test measuring the LoS, 22 fundamental differences are present between FRT and LoS. Unlike LoS, FRT measures trunk flexibility as well as LoS.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that FRT scores were significantly higher in runners with ID compared to their sedentary counterparts. The FRT reflects flexibility, particularly the range of motion of the shoulder and/or hip joints, that largely influence the participants’ reaching distances, because the motion of this task requires maximal extension of the extremities and a large flexing action of the hip and shoulder joints (Uchiyama et al, 2011). In this context, runners had greater flexibility, as might be predicted by the fact that, when running at high speed, the legs go through a certain motion in which the knee drives upward and the heel comes up under the butt like when stepping over something of hip height (Majumdar & Robergs, 2011; Mero et al, 1992).…”
Section: Discussionmentioning
confidence: 99%